2014
DOI: 10.3906/tar-1401-126
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid performance and heterosis in F1 offspring of triticale (× Triticosecale Wittm.)

Abstract: In this study, the combined ability effects and heterosis were determined for number of days to anthesis (AT), plant height (PH), fertile tillers plant -1 (FT), spike length (SL), spikelets spike-1 (SS) and grains spike -1 (GS), 1000-kernel weight (TW), and grain yield plant -1 (GY) of 4 triticale genotypes [Karma (G1), Presto (G2), Ayşehanım (G3), and Mehmetbey (G4)] and their 6 F 1 offspring. The mean squares of general combining ability (GCA) and specific combining ability (SCA) were statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Fischer et al (2010) mention that the prediction of the heterosis based on the parents averages of a single cross result in low precision, and in such a case, it would be advisable to carry out a general and specific combining ability analysis. Other authors (Oettler et al 2001;Cifci and Yagdi 2007;Yildirim et al 2014) have reported similar values of heterosis and heterobeltiosis in triticale. Traits that presented inbreeding depression were SP (-21.6), SL (-2.52), SS (-3.29), SG (-5.99) and GY (-26.64).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Fischer et al (2010) mention that the prediction of the heterosis based on the parents averages of a single cross result in low precision, and in such a case, it would be advisable to carry out a general and specific combining ability analysis. Other authors (Oettler et al 2001;Cifci and Yagdi 2007;Yildirim et al 2014) have reported similar values of heterosis and heterobeltiosis in triticale. Traits that presented inbreeding depression were SP (-21.6), SL (-2.52), SS (-3.29), SG (-5.99) and GY (-26.64).…”
Section: Resultssupporting
confidence: 59%
“…The analysis of the nature and magnitude of the gene effects on quantitative traits helps the researcher to design an efficient improvement program and to provide information on the potential manifestation of heterosis (Shekhawat et al 2000). Analysis of relative mid-parent heterosis (Mh%) and heterobeltiosis (Hh%) allows to define the breeding strategy (Yildirim et al 2014). Recent studies in triticale suggest that hybrids performance are significantly higher than cultivated varieties (Oettler et al 2003;Yildirim et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive combining ability is an indicator of an increase in a trait under study and a negative result indicates a decrease in the performance of the trait [47] . In this study we assessed the sprouting resistance by GI and PG.…”
Section: Discussionmentioning
confidence: 99%
“…To transfer desired characters to offspring, those parents that have a good combining ability should be included in a compound breeding approach [48] . Yildirim et al [47] stated that the additive genetic variation is the main choice in formalizing a selection approach in a wheat breeding program. Among the genotypes, Doukkala-12 and BARS-09, showed significant negative GCA values for PG and GI.…”
Section: Discussionmentioning
confidence: 99%